Dietary Intake and Nutritional Status of Dialysis and Non-dialysis Patients in Selected Specialized Hospitals of Dhaka City - Amin, Md Ruhul; Haque, Mahmuda; Syed, Mahfuz Al Hasan; Ali, Masum; Nawaz, Md Sameul; Chowdhury , Tasneem Hasin (Bangladesh Journal of Nutrition, 2014)
The objective of this cross-sectional study was to evaluate dietary intake and nutritional status of chronic renal failure patients with and without dialysis. A total of 105 subjects from three different specialized hospitals located in Dhaka city were included in this study. The subjects were selected purposively. Fifty-nine patients were on dialysis whose median age was 56 years, and forty-six patients were without dialysis whose median age was 52 years. An interviewer administered questionnaire was developed to obtain socio-demographic, anthropometric, and dietary data. Dietary intake was obtained by 24-hour recall. The findings of this study showed that 8.5% of the patients on dialysis were underweight and 39% were overweight while prevalence of underweight and overweight in non-dialysis patients was the same (17.4%). More than 40% of these chronic renal failure patients were found to have no knowledge about potassium rich foods and only 20% were found to have good knowledge about potassium rich foods. Majority of the patients (about 70%) do not have knowledge about uric acid rich foods irrespective of dialysis and non-dialysis condition. Mean intake of different food groups were not significantly different between two groups except that egg consumption was significantly higher (/7=0.01) for dialysis group. Estimated average energy intake was about 17kcal/kg/day in dialysis patients and 18kcal/kg/day in non-dialysis patients. Mean protein intake was 0,95g/kg/day in dialysis and 0.85g/kg/day in non-dialysis patients. No significant difference regarding macro and micro nutrients intake was observed between two groups. All the patients were found to have lower intake of energy than the recommended level. About 68% of dialysis patients and 76% of non-dialysis patients were found to have protein intake below the recommended level. It can be concluded that prevalence of overweight was high in dialysis patients while malnutrition was prevalent in non-dialysis patients. Knowledge about the sources of potassium and uric acid rich-food amongst the subjects was very poor. The consumption of nutrients among the patients belonging to both groups was also grossly inadequate and below the recommended level. Bangladesh J. Nutr. Vol. 26-27, December 2014, P: 41-51